Diversity of 17 Genotypes of Taro Based on Anatomy and Nutritional Value of Tuber - Cahyanti, Lutfy Ditya; Didy Sopandie; Edi Santosa; Heni Purnamawati (HAYATI Journal of Biosciences, 2024)
Indonesia is one of the countries with the greatest diversity of taro variety, while the study of taro's morphology and nutritional characteristics is limited. The aim of this study was to evaluate the anatomical of plant and nutritional value of taro tuber. This research observed fourteen genotypes of Colacasia esculenta (7 Eddoe types, 7 Dasheen types) and 3 Xanthosoma genotypes. In three blocks of replications, the eddoe and Xanthosoma genotypes were cultivated using cormel and the dasheen genotypes with sucker. Plant anatomy (leaf, stem, and root) and tuber nutritional characteristics were analyzed. From this research, explained that stomata and epidermis number, length from stomata and epidermis, number leaf epidermis, length of leaf and stem epidermis, also length of root epidermis, endodermis, cortex, and stele among 17 genotypes of taro were statistically different. The diversity of taro based on the nutrition content of tuber between 17 genotypes of taro was considered high, as represented by water, ash, fat, protein, carbohydrate, energy, and glucomannan, which were statistically different.